2019
DOI: 10.1093/ageing/afz128
|View full text |Cite
|
Sign up to set email alerts
|

Informal caregiving for dementia patients: the contribution of patient characteristics and behaviours to caregiver burden

Abstract: Objectives The burden often associated with informal caregiving for patients with dementia is associated with negative effects on health, both physiologically and in terms of caregiver cognition. There is wide variation in the level of burden experienced by dementia caregivers. To better understand caregiver burden, it is thus important to understand the factors associated with level of burden. Methods In the current study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 20 publications
0
43
0
2
Order By: Relevance
“…During the confinement, the caregivers have increased the time of care by facing the additional security measures and dealing with the fear of not being infected to safeguard the health of their family members; associated factors with increased caregiver burden [6]. Difficult access to support services has caused the breakdown of established routines with consequent negative effects for both parties.…”
Section: Introductionmentioning
confidence: 99%
“…During the confinement, the caregivers have increased the time of care by facing the additional security measures and dealing with the fear of not being infected to safeguard the health of their family members; associated factors with increased caregiver burden [6]. Difficult access to support services has caused the breakdown of established routines with consequent negative effects for both parties.…”
Section: Introductionmentioning
confidence: 99%
“…10 The burden experienced by caregivers has many causes, such as the constant and increasing need to supervise the patient, the older adult's physical and cognitive dependence, the lack of support from other family members, family conflicts, financial difficulties, and social deprivation. 11,12 Researchers have shown that NPSs of an older adult affected by AD are some of the main determinants of caregiver burden. 11,13 NPSs are reported as more stressful for caregivers than cognitive and functional problems, perhaps due to the unstable nature of these symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Researchers have shown that NPSs of an older adult affected by AD are some of the main determinants of caregiver burden. 11,13 NPSs are reported as more stressful for caregivers than cognitive and functional problems, perhaps due to the unstable nature of these symptoms. While the functional and cognitive trajectories of the patient with dementia follow a constant and expected decline, behavioral problems may fluctuate, which may leave the caregiver less prepared to deal with them properly.…”
Section: Introductionmentioning
confidence: 99%
“…Family or friends are often key informal caregivers for people living with dementia [8,9]. Globally, over 80 billion hours of informal care is provided to people living with dementia [5,10].…”
Section: Introductionmentioning
confidence: 99%